Findings from the 2017 Yearbook Section on Health Information Management - Bloomrosen, M.; Berner, E. S.; Section Editors for the IMIA Yearbook Section on Health Information Management (Yearbook of Medical Informatics, 2017)
Objectives: To summarize the recent literature and research and present a selection of the best papers published in 2016 in the field of Health Information Management (HIM).Methods: A systematic review of the literature for the IMIA Yearbook HIM section was performed by the two section editors with the help of a medical librarian. We searched bibliographic databases for HIM-related papers were searched using both MeSH headings and key words in titles and abstracts. A shortlist of candidate best papers was first selected by section editors before being peer-reviewed by independent external reviewers.Results: The five papers selected as ‘Best Papers’ illustrate a variety of themes, include authors from a variety of countries, and were published in some of the best journals in the field. The themes of the five best papers include health information exchange, personal health records, patient engagement, data quality, and e-quality measures.Conclusions: The discipline of Health Information Management is increasingly becoming allied with the field of Biomedical Informatics in that both disciplines have interests in common. Traditional HIM areas of expertise (in the pre-electronic health record world), such as coding and privacy and security of health information, are necessary for the electronic exchange and secondary use of health information. With the changes in healthcare delivery brought by the use of electronic health records, addressing issues of information governance is essential. This synopsis discusses these key issues at the intersection of HIM and informatics, examines the potential challenges, and points the way for best practices, future research, and public policy considerations and directions.
Keywords: Health Information Management; health information exchange; personal health records; health informatics; secondary data use